ASSOCIATION OF GENETIC POLYMORPHISMS IN THE Matrix Gla Protein (MGP) GENE WITH CORONARY ARTERY DISEASE AND SERUM MGP LEVELS - LÜLECİ, NİMET EMEL; KARSLI, SEHER; YURDUN, TÜRKAN; KESKİN, YAŞAR (MACEDONIAN ACAD SCIENCES ARTS, 2019)
Matrix Gla protein (MGP) is an important regulatory protein for inhibition of calcification in the vessel wall and cartilage. The MGP gene polymorphisms are suspected to increase the risk of extracellular calcification through altering the related gene expression and serum MGP levels. The goal of this study was to examine the correlation between rs4236 (Thr83-Ala), rs12304 (Glu60-X) and rs1800802 (T138-C) polymorphisms of the MGP gene and coronary artery calcification. Serum MGP levels of 168 subjects who had undergone coronary angiography were analyzed along with genotyping of MGP gene polymorphisms. The results indicated that serum MGP levels were significantly associated with rs4236 and rs1800802 polymorphisms of the MGP gene with the occurrence of coronary artery diseases (CAD). Allelic distributions of MGP gene polymorphisms and serum MGP levels, respectively, were not significantly interconnected with the presence of CAD. Our results revealed that serum MGP levels of CAD patients show association with rs4236 and rs1800802 polymorphisms, but serum MGP levels alone do not directly reflect the risk of CAD. The role of MGP genetic variants on formation and progression of arterial calcification should be regarded in cardiovascular diseases.
Keywords: Cardiovascular disease; Coronary artery disease (CAD); Genetic polymorphism; Matrix Gla protein (MGP); CALCIFICATION; MORTALITY; VARIANTS; MEDIA; RISK